Evaluación de la concentración de material particulado pm10 y pm2.5 generado en fuentes fijas por la elaboración de bloques de cemento en la parroquia Pastocalle cantón Latacunga provincia de Cotopaxi en el periodo 2020 - 2021. - Iza Montatixe, Carlos Paul (2021)
This research was developed with the objective of evaluating the concentrations of Particulate Material PM10 and PM2.5; in the Pastocalle Parish, Latacunga Canton, Province of Cotopaxi, to establish if negative environmental impacts are being generated to the atmosphere or to the environmental air resource in the sectors of the study area, produced by the emission of solid particles, by the small industries that are dedicated to the manufacture of cement blocks, which can cause discomfort to the inhabitants of the Parish and induce adverse environmental effects to the environment. The study area was characterized through in-situ visits in the different sectors of the Pastocalle Parish to carry out the proper monitoring of the PM10 and PM2.5 Particulate Material; which were carried out in 5 strategic points of the study line which were the following: “El Progreso” sector (P1) with the coordinates (E: 764913; N: 9919083); “El Boliche” sector (P2) with the coordinates (E: 766119; N: 9921413); “Cuilche Salas” sector (P3); with the coordinates (E: 766251; N: 9921222); “El Boliche” sector (P4); with the coordinates (E: 766875; N: 9921284); “El Chasqui” sector (P5); with the coordinates (E: 767320; N: 9921076); it was performed during the 24 hours for ten days to determine the existing concentrations in the day and at night, by obtaining probabilistic data sampled with the help of the E-BAM equipment. With the monitoring data, a data base was created, which were tabulated and compared with the Ecuadorian Environmental Regulation of Air Quality TULSMA, Book VI, Annex 4 and with the reform of Ministerial Agreement 097, the information obtained allowed to know the concentration levels of Particulate Material PM10 and PM2.5, in the different established points that were: “El Progreso” sector (P1); with a concentration value of 26 μg/m3 of PM10 and 25 μg/m3 of PM2.5; in the “El Boliche” sector (P2); with a concentration value of 23 μg/m3 of PM10 and 24 μg/m3 of PM2.5; in the “Cuilche Salas” sector (P3); with a concentration value of 58 μg/m3 of PM10 and 24 μg/m3 of PM2.5; in the “El Boliche” sector (P4); with a concentration value of 28 μg/m3 of PM10 and 18 μg/m3 of PM2.5; and finally in “El Chasqui” sector (P5); with a concentration value of 46 μg/m3 of PM10 and 24 μg/m3 of PM2.5, which are within the maximum permissible limits according to current regulations.